2013
DOI: 10.1371/journal.pone.0070483
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations and Abnormal Mitosis of Wheat Chromosomes Induced by Wheat-Rye Monosomic Addition Lines

Abstract: BackgroundWheat-rye addition lines are an old topic. However, the alterations and abnormal mitotic behaviours of wheat chromosomes caused by wheat-rye monosomic addition lines are seldom reported.Methodology/Principal FindingsOctoploid triticale was derived from common wheat T. aestivum L. ‘Mianyang11’×rye S. cereale L. ‘Kustro’ and some progeny were obtained by the controlled backcrossing of triticale with ‘Mianyang11’ followed by self-fertilization. Genomic in situ hybridization (GISH) using rye genomic DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 34 publications
(40 reference statements)
0
37
0
Order By: Relevance
“…On this account, there were minor differences among 4844-12, 5113, and 5114, which belong to 6 P I . In addition, we found that elimination of repetitive sequences on some chromosomes of ABD genomes was present in 4844-12 (unpublished results), and this situation could also be found in wheat–rye monosomic addition lines [72]. Elimination of DNA sequences might be the common form of rearrangements in addition line.…”
Section: Discussionmentioning
confidence: 67%
“…On this account, there were minor differences among 4844-12, 5113, and 5114, which belong to 6 P I . In addition, we found that elimination of repetitive sequences on some chromosomes of ABD genomes was present in 4844-12 (unpublished results), and this situation could also be found in wheat–rye monosomic addition lines [72]. Elimination of DNA sequences might be the common form of rearrangements in addition line.…”
Section: Discussionmentioning
confidence: 67%
“…These changes may trigger complicated interactions between the repair of DNA damage and the regulation of cell cycles. Another aspect of genome shock maybe also include parentage-biased patterns of gene expression and the abnormal upand down-regulation of offspring genes and abnormality in the very nascent hybrid genomes: e.g., 2nF 1 and 2nF 2 (59,60). We hypothesize that the alteration of expression of these genes drives polyploidization.…”
Section: Discussionmentioning
confidence: 97%
“…pHvG38, pSc119.2, and pDb12H were labeled with Taxas-red-5-dUTP (Invitrogen) by nick translation. Probe labeling and hybridization were as described by Fu et al [2013]. Microphotographs of C-banded and FISH chromosomes were taken with an Olympus BX-51 microscope equipped with a DP-70 CCD camera.…”
Section: C-banding and Fishmentioning
confidence: 99%